PENGUATAN KESEHATAN LANSIA MELALUI PEMERIKSAAN GLOCOSE, CHOLESTROL DAN URID ACID PADA JEMAAT GPI PAPUA BETHLEHEM SORONG - Edward Clant; Ade Andriani Renouw; Andrey Maryen; Lili Sarce Joi Sapari; Yunika Upa (SOLIDEO Jurnal Pengabdian Masyarakat, 2023)
The elderly are one of the groups or populations at risk that are increasing in number. Allender, Rector and Warnes (2014) in Khusnul, Mila (2020) say that the population at risk is a collection of people whose health problems are likely to develop worse because of the risk factors that influence them. This community service aims to increase empathy and concern for university personnel to the problems faced by church institutions; provide an understanding of the importance of maintaining a healthy body in the elderly; instilling the values ​​of love, caring, appreciating and respecting parents, as well as the importance of maintaining a healthy lifestyle as early as possible. Implementation of activities in the form of health checks for members of the elderly congregation of the GPI Papua Bethlehem Sorong congregation with the elderly category. It is hoped that this medical examination will have a good influence on the congregation in maintaining health and it has been proven from the enthusiasm that the number of participants involved in the medical examination has reached 42 people.